Tanggung Jawab Orang Tua Dalam Pendidikan Anak (Studi Kasus Keluarga Nelayan Tengah) - Oktaviana, Oktaviana (UNIVERSITAS TANJUNGPURA, 2014)
The purposes of this research are to describe the parents’ responsibility in religion education, moral education, physical education and intelligence education to the children of sailor family Kelurahan Tengah Kecamatan Delta Pawan Kabupaten Ketapang. Method of this research is descriptive method by using case study. The participant informant is sailor family who has children in elementary school age that don’t continue the study to the junior high school. The result from this research is parents’ responsibility in children education do not understand by the parents such as : 1). In religion education the parents never teach to pray and read read AL-Qur’an, and parents do not transfer their children to TPA, 2). In moral education the parents teach their children to be kind to anyone but they do not apply it in their daily life, 3). In physical education the parents not really care about keeping clean and health, 4). In intellectual education the parents have lack motivation to their children to finish their study in high level. Keywords : Responsibility, Parents, Children Education.